MOH SJAFEI'S TAXONOMY: BRAIN, HEART, AND HAND LEARNING - Afdhal Afdhal (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This article aims to find the threads of Moh Sjafei’s educational concept, including the taxonomy of learning and its educational philosophy. The term learning taxonomy itself has been more popularly used by Bloom since 1956. However, far from that, in practice and the concept has been introduced by Moh Sjafei through the Kayutanam INS since 1926. The research method used is a qualitative research method with a type of literature study. This study found that there are three dimensions of Moh Sjafei’s taxonomy of learning, namely the dimensions of the brain, heart, and hands. The dimensions of the brain have several levels, starting from insight, habits, innovation, and production. Meanwhile, the heart dimension covers art, religion, and society. Whereas, the hand dimension covers the learning of skills that can liberate students' souls. These three parts must be balanced and applied in the learning process. Meanwhile, educational philosophy as the basis of Sjafei's taxonomic concept is the philosophy of pragmatism. The conclusion of this article is Sjafei's taxonomy with the dimensions of the brain, heart, and hands, as well as the philosophy of pragmatism as the key concepts of his educational thinking.